ANALISIS SPASIAL PEMETAAN PEMUKIMAN WARGA PADA AREA RAWAN BENCANATANAH LONGSOR DI KOTA SEMARANG - Rohmat Abidin; Sri Yulianto JR (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
Semarang city has a diverse land contours. However, people do not know that the area for residence is located in the area prone to landslides. Spatial analysis became one of the alternatives for conducting the mapping process of landslide prone areas. Spatial is one technique by involving a number of calculations and logic evaluations done in order to find or discover the potential relationships or patterns that exist between the geographic elements contained in the digital data. Processed data are contour, rainfall, earthquake, soil movement, land use, rock type, population data and resident data. The result of this mapping process resulted in the information of the residential area in the very vulnerable zone of the landslide 2%, landslide-prone zones 5% and moderately vulnerable zones 7%.